Characterization of Social Representations of Intragender Violence in Couple of Gay Men: Caso: Ciudad de Temuco-Chile - Franco Saavedra, María Angélica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present article is in charge of studying the intra-gender violence that is manifested in couples of gay men, and how it is socially represented in the commune city of Temuco-Chile. For this, the objective is the characterization of said violence, comprising an applied investigation in an age range of 18-50 years during the period of 2020-2021. Among the results obtained in this investigation, serious consequences stand out in cases of intra-gender violence, the fear of reporting the abuse for fear of aggression, and the negligence of the authorities in giving importance to said phenomenon.